2019
DOI: 10.1088/1757-899x/697/1/012031
|View full text |Cite
|
Sign up to set email alerts
|

A review of accidents & incidents on Boeing and Airbus commercial aircraft’s avionics-related system in two decades (1996-2015)

Abstract: Aviation accidents still hit the news even though the growth of technological advancement on commercial aircraft avionic systems has been impressive. Hence, one of the objectives of this study is to plot the time-based graph of commercial aviation accidents, with direct consequence from avionics instrumentations in the period of two decades, from 1996 to 2015. The second objective is to analyse two main aircraft manufacturers, Boeing and Airbus, in determining specific model of its kind that significantly invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Relative to all other manufactures, previous studies have shown that both Boeing and Airbus perform better [13]. The conclusion that suggests Airbus is performing better than Boeing in terms of safety mirrors previous studies [14,15]. A reader may ask the question, what would happen if the "anomalous" data points of the Boeing 737MAX were removed?…”
Section: Accident Ratementioning
confidence: 63%
See 1 more Smart Citation
“…Relative to all other manufactures, previous studies have shown that both Boeing and Airbus perform better [13]. The conclusion that suggests Airbus is performing better than Boeing in terms of safety mirrors previous studies [14,15]. A reader may ask the question, what would happen if the "anomalous" data points of the Boeing 737MAX were removed?…”
Section: Accident Ratementioning
confidence: 63%
“…The study showed that in a direct comparison, correcting for fleet size, the probability of an accident occurring was greater for Boeing than for Airbus. A related study looked at accidents only involving avionic systems [15]. This noted that while the Boeing 737 was more frequently associated with these accidents, most of these were still attributed to human factors, highlighting the critical role of the end user.…”
Section: Introductionmentioning
confidence: 99%